Women Education for Social, Economic and Political Development in Kenya - Yungungu , Alice; Mulinge , Patrick; Ogolla , Bernard (African Journal of Education,Science and Technology (AJEST), 2025)
Various national regional and international conventions and documentation have emphasized that enabling the population regardless of gender to actively participate in social and economic well being is critical for long term and sustainable social, politica l and economic development of any society. One way of empowering the population is through education. Education is the process by which people acquire knowledge, skills, values and attitudes by which they develop an appreciation of their cultural values, through which all these are passed from one generation to the other. Education is the true bedrock of the society‟s culture, civilization and a powerful tool for perpetuating social, political and economic development. As such, education is pivotal to overa ll development of humankind. According to the human capital theory, “The greater the investment in education, the greater the collective benefits to the society and the greater the benefit the participants are likely to get.” Further, the collective benefi ts for the society increase with higher participation of women in education. For over a decade now, educating girls/women has been identified to have both direct and indirect benefits. Improved maternal health, lower incidences of HIV/AIDS, poverty reduction and environmental protection are but some of the positive outcomes when girls/women are educated. The impact of educating women actually goes beyond them and their family to enrich the entire nation. It is in the light of this that this paper seeks to d iscuss the diverse social, political and economic benefits that accrue from educating women. Based on the discussions, recommendations will be made that will go a long way to enhance women education in general and particularly in Kenya.